PENGARUH BUDAYA ORGANISASI DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PADA BPJS KETENAGAKERJAAN CABANG BELAWAN - Faustyna Faustyna (Universitas Medan Area, 2015)
Performance is an overview of the level of achievement of the implementation of a program of activities or policies in realizing the goals, objectives, vision and mission of the organization that poured through the organization's strategic planning. Companies should establish performance standards to its employees, especially in the factors that affect the performance. The purpose of this study is per first to investigate the influence of organizational culture on performance, both to determine the effect on the performance of the work ethic, and the third to know the influence of organizational culture and work ethic together on employee performance on BPJS Employment Branch Belawan. The method in this study using a quantitative approach. With this type of associative research. The sample used is an overall object of the study population numbering 33 people. Collecting data in this study using a questionnaire / questionnaire with Likert scale. Based on research results by using the t test explains that there is a significant influence of organizational culture on employee performance with the value t count> t table which significantly by 4,223> 2.04 with a significant 0,000 <0,05 and work ethic have a significant effect on performance employees with t count> t table which is equal to 4.910> 2.04 with a significant 0.000 <0.05. And there is the influence of organizational culture and work ethic together on employee performance based on test results conducted by F obtained F count> F table which amounted to 15.653> 3.32 using a 95% confidence level or α = 0.05.